Brex and the city. Cultural references in British, Polish and German Newspaper Articles on the British EU Referendum - Miller, Dorota (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Socially produced ideas can be tracked in individual texts or groups of texts, especially media texts commonly regarded as “[…] moments when the larger social and political structures within the culture are exposed to analysis” (Turner 1996: 88). This inextricable connection between media and culture in modern societies is reflected in the interdisciplinary field of research known as the study of media culture (cf. Kellner 1995), Medienkulturwissenschaft (cf. Schmidt 2003) or kulturoznawcze medioznawstwo (Gwóźdź 2008). Following this, the focus of attention of this study are examples of intra- and cross-cultural intertextuality in British, German and Polish Brexit-related newspaper articles.

Idee wytwarzane przez społeczeństwo można prześledzić w poszczególnych tekstach lub grupach tekstów, zwłaszcza w tekstach medialnych powszechnie uznawanych za „[...] momenty, w których większe struktury społeczne i polityczne w kulturze są poddane analizie” (Turner 1996: 88). Ten nierozerwalny związek między mediami i kulturą we współczesnych społeczeństwach znajduje odzwierciedlenie na interdyscyplinarnym polu badań, znanym jako studium kultury medialnej (por. Kellner 1995), Medienkulturwissenschaft (por. Schmidt 2003) czy kulturoznawcze medioznawstwo (Gwóźdź 2008). Następnie na pierwszy plan wysuwają się przykłady wewnątrzkulturowej i międzykulturowej intertekstualności w brytyjskich, niemieckich i polskich artykułach prasowych związanych z Brexitem.
Brex and the City. Kulturowe odwołania do brytyjskiego referendum w sprawie wyjścia z UE w prasie brytyjskiej, polskiej i niemieckiej
Keywords: cultural references; intertextuality; Brexit; mass media; odniesienia kulturowe; intertekstualność; Brexit; mass media